Easy Indian cooking : 101 fresh & feisty indian recipes / Hari Nayak ; photography by Jack Turkel - Nayak, Hari
"In Easy Indian Cooking, Chef Hari Nayak presents recipes for the dishes he remembers from childhood days, growing up in rural southern India. These recipes have been modified to suit a modern lifestyle, and all of them can be prepared with ingredients available at any local supermarket or health food store. The preparation and cooking techniques have been simplified to save time without sacrificing any of the authentic Indian flavor."